PATTERN OF MANDIBULAR THIRD MOLAR IMPACTION: A RADIOGRAPHIC STUDY - Rauf, Sana; Ali, Waqar; Tariq, Qunoot; Chaudhry, Rabia; Kazmi, Syeda Sadaf; Imtiaz, Muhammad (Pakistan Oral & Dental Journal, 2019)
Impacted teeth, if left untreated, have potential to induce various complications. The aim of the current study was to determine the prevalence and pattern of impacted mandibular third molar in a Pakistani population. This retrospective study evaluated 601 panoramic radiographs of selected patients. Data were collected regarding age and gender, prevalence of impacted mandibular third molars, angulation of impacted teeth, level of impaction, and relationship of the mandibular third molar with the ramus. The mean age of patients was 32.90 ± 11.24 years (range 16 to 81 years). A significant association was observed between gender and impaction of mandibular thirs molars (p < 0.05). The most common kind of impaction in the mandible was mesioangular, followed by vertical, horizontal and distoangular impaction.